Association of NR3C1/Glucocorticoid Receptor gene SNP with azoospermia in Japanese men. Issue 1 (10th November 2015) - Chihara, Makoto; Yoshihara, Kosuke; Ishiguro, Tatsuya; Adachi, Sosuke; Okada, Hiroyuki; Kashima, Katsunori; Sato, Takaaki; Tanaka, Atsushi; Tanaka, Kenichi; Enomoto, Takayuki
Abstract: Aim: The molecular pathogenesis of non‐obstructive azoospermia (NOA) is unclear. Our aim was to identify the genetic susceptibility for NOA in Japanese men by using a combination of transcriptome network analysis and SNP genotyping. Material and Methods: We searched for candidate genes using RNA transcriptome network analysis of 2611 NOA‐related genes that we had previously reported. We analyzed candidate genes for disease linkage with single nucleotide polymorphisms (SNP) in the genomes of 335 Japanese men with NOA and 410 healthy controls using SNP‐specific real‐time polymerase chain reaction TaqMan assays. Results: Three candidate genes ( NR3C1, YBX2, and BCL2 ) were identified by the transcriptome network analysis, each with three SNP. Allele frequency analysis of the nine SNP indicated a significantly higher frequency of the NR3C1 rs852977 G allele in NOA cases compared with controls (corrected P = 5.7e‐15; odds ratio = 3.20; 95% confidence interval, 2.40–4.26). The other eight candidate polymorphisms showed no significant association. Conclusion: The NR3C1 rs852977 polymorphism is a potential marker for genetic susceptibility to NOA in Japanese men. Further studies are necessary to clarify the association between the NR3C1 polymorphism and alterations of glucocorticoid signaling pathway leading to male infertility.